School-aged children learning second language sounds: The Effects of different learning backgrounds on children’s second language sound production and perception learning - Haapanen, Katja (fi=Turun yliopisto|en=University of Turku|, 2021)
Earlier phonetic research on children’s second language sound learning has primarily focused on naturalistic language learning environments and the comparison of child and adult learners. The aim of this thesis was to examine how 6–13-year-old Finnish children with different learning background factors learn to perceive and produce second language sounds in instructed settings and phonetic training contexts. The background factors examined in Studies I–IV of this thesis were age, language immersion education and music-oriented education. The aim of Study I was to discover how passive auditory training affects 7–12-year-old children’s non-native sound perception. The results showed that the older participants’ (9–12 years) perceived the trained non-native sound after passive auditory training. Study II examined how studying in a language immersion program in elementary school affects 11–13-year-old children’s second language pronunciation. The findings suggest that studying in a language immersion program results in more accurate second language pronunciation when compared to nonimmersive learning. Study III investigated how music-oriented education in elementary school affects 9–11-year-old childen’s ability to learn non-native sound production through auditory training. No significant effects of music-oriented education were found. Study IV aimed to discover how listen-and-repeat training affects 6–7-year-old preschoolers’ non-native sound production. The results showed rapid changes in production after minimal amount of listen-and-repeat training. Overall, the results of Studies I–IV suggested that age of learning has the strongest effect on school-aged children’s second language sound learning.

Kouluikäiset lapset oppimassa vieraan kielen äänteitä: Erilaisten oppimistaustojen vaikutus lasten vieraan kielen äänteiden tuoton ja havaitsemisen oppimiseen Aiemmat lasten vieraan kielen äänteiden oppimista selvittävät foneettiset tutkimukset ovat pitkälti keskittyneet luonnollisiin kielenoppimisympäristöihin sekä lapsi- ja aikuisoppijoiden vertailuun. Tämän tutkielman tavoite oli selvittää, kuinka erilaiset oppimisen taustatekijät vaikuttavat 6–13-vuotiaiden suomenkielisten lasten vieraan kielen äänteiden havaitsemisen ja tuoton oppimiseen. Tarkasteltavat taustatekijät olivat ikä ja kieli- tai musiikkiluokalla opiskelu. Tutkimus koostui neljästä osatutkimuksesta. Tutkimuksessa I selvitettiin passiivisen auditorisen treenin vaikutuksia 7–12-vuotiaiden lasten vieraan kielen äänteen havaitsemiseen. Tulokset osoittivat, että vanhemmat (9–12 vuotta) osallistujat havaitsivat treenatun vieraan kielen äänteen passiivisen kuuntelun jälkeen. Tutkimuksessa II tarkasteltiin peruskoulun kieliluokalla opiskelun vaikutuksia 11–13-vuotiaiden lasten vieraan kielen ääntämiseen. Tulokset viittasivat, että kieliluokalla opiskelu johtaa parempaan ääntämistarkkuuteen kuin perinteinen luokkahuoneoppiminen. Tutkimuksen III tavoite puolestaan oli selvittää, vaikuttaako musiikkiluokalla opiskelu 9–11-vuotiaiden lasten kykyyn oppia tuottamaan vieraan kielen äännekontrasti auditorisen treenin avulla. Musiikkiluokalla opiskeluun liittyviä merkitseviä eroja tuoton oppimisessa ei löydetty. Tutkimuksessa IV selvitettiin, kuinka kuuntele-ja-toista treeni vaikuttaa 6–7-vuotiaiden esikoululaisten vieraan kielen äännekontrastin tuottoon. Tulokset osoittivat, että esikoululaiset muuttivat tuottoaan nopeasti vähäisen harjoittelun jälkeen. Kokonaisuudessaan tutkimuksen tulokset antoivat viitteitä siitä, että oppimisikä vaikuttaa kouluikäisten lasten vieraan kielen äänteiden oppimiseen voimakkaammin kuin muut tarkastellut taustatekijät.